Pengaruh Disiplin Kerja, Motivasi Dan Nilai-Nilai Sosial Terhadap Kinerja Pegawai Pada Dinas Pemadam Kebakaran Dan Penyelamatan Jakarta Timur - Widi Astuti; Zaharuddin Zaharuddin; Nurmansyah Nurmansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of work discipline, motivation, and social values on employee performance in the fire and rescue service in East Jakarta. The background of this study is based on the importance of employee performance in supporting public services. The method used is s descriptive verification with a quantitative approach; the sample in this study was 60 people in the fire and rescue service. The analysis technique uses the SPSS version 28 computer application program. The result of the study shows the influence of the three variables. That work discipline, motivation, and social values have a positive effect on employee performance. Work Motivation has the most dominant influence compared to other variables; this finding indicates that increasing work discipline and motivation and strengthening social values can significantly improve employee performance.